Pembiasaan Hafalan Surat Pendek Al-Qur’an Melalui Media Berbasis Teknologi Untuk Meningkatkan Prestasi Siswa - Nenok Rahmawati; Sofyan Sauri; Ahmad Sukandar (Peneliti.net, 2022)
Learning planning, implementation, evaluation/assessment, supporting and inhibiting factors as well as solutions that are often applied are not in accordance with curriculum guidelines at the Raudhatul Athfal level. This type of research uses a qualitative descriptive approach to field research (field research) which takes the research location in RA Bany Radhiya, Bandung Regency. Data collection techniques with observation, interview and documentation techniques. The results of the study show, (1) that preparation is always carried out with head and teacher meetings to prepare the curriculum. Implementation is carried out every day fifteen minutes before the main activity and evaluates each activity completion by conducting a checklist assessment, as well as minimizing inhibiting factors by finding solutions, showing that this memorization habit has many benefits, as a solution. (2) the habit of memorizing short letters of the Qur'an through technological media can take place anywhere, in the classroom, outside the classroom, offline or online. The introduction of technology from an early age can support the achievement of educational goals that make graduates fear God Almighty. The implication of this habit is to increase academic and non-academic achievements and recommendations for all foundations, institutions, heads, teachers and parents to straighten their intentions in guiding as a field of worship.